Immunobiological Properties of Francisella tularensis 15/10 Strain with Deleted recA Gene - A. A. Lapin; A. N. Mokrievich; G. M. Vakhrameeva; T. I. Kombarova; I. V. Bakhteeva; I. A. Dyatlov; V. M. Pavlov (Проблемы особо опасных инфекций, 2011)
Deletion of recA gene in Francisella tularensis 15/10 genome leads to the increase in its sensitivity to ultraviolet irradiation, reduction of the homologous recombination capacity, and a slight decline of virulence for mice. Efficacy of Francisella tularensis 15/10ΔrecA reproduction within microphage-like cells, its resistance to normal rabbit serum, and protective properties on the mouse model of tularemia are the same as in original Francisella tularensis 15/10.